Attention deficit hyperactivity disorder - Watkins, Heidi (Detroit : Greenhaven Press, 2011)
Several articles deal with issues surrounding ADHD.
Bibliographical : p. 125-127
Keywords: Attention-deficit hyperactivity disorder -- Juvenile literature; Attention deficit disorder with hyperactivity; Child; Adolescent; Adult